1999
DOI: 10.1074/jbc.274.48.34375
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Nucleoside Diphosphate Kinase-like Activity Is a Novel Function of the 20 S Proteasome

Abstract: The eukaryotic 20 S proteasome is the prototype of a new family of the N-terminal nucleophil hydrolases and is composed of numerous low molecular mass subunits arranged in a stack of four rings, each containing seven different ␣-or ␤-subunits. Among the ␤-type subunits in the yeast proteasome, three proteolytically active ones were identified, although the functions of the other ␤-and ␣-type subunits remain to be clarified. We report here that the purified 20 S proteasome exhibits intrinsic nucleoside diphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…On the other hand, several studies have shown that protein phosphorylation at serine residues is a signal that triggers proteolysis by the proteasome [66][67][68]. In 1999, Yano et al [69] reported a new function for the purified 20S proteasome obtained from a human lymphoblastoma cell line. They demonstrated that the proteasome exhibits intrinsic nucleoside diphosphate kinaselike activity.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, several studies have shown that protein phosphorylation at serine residues is a signal that triggers proteolysis by the proteasome [66][67][68]. In 1999, Yano et al [69] reported a new function for the purified 20S proteasome obtained from a human lymphoblastoma cell line. They demonstrated that the proteasome exhibits intrinsic nucleoside diphosphate kinaselike activity.…”
Section: Discussionmentioning
confidence: 97%
“…Histidine phosphorylation events are difficult to detect. Other mammalian signaling proteins have been reported to exhibit histidine phosphorylation, including the ␤ subunit of heterotrimeric G proteins (113)(114)(115), annexin I (116), and the 20 S proteasome (117), and suggest that more involved signaling pathways may also exist.…”
Section: Interaction Of the Ksr 14-3-3 Binding Sites And Serine 434 -mentioning
confidence: 99%
“…NDK is involved in the proteolytic functions of the proteasome. It may act by catalyzing the activities of ATP hydrolysis when Hsp70 and VCP/ p97 are activated (Yano et al 1999). Meanwhile, (Kimura et al 2003) reported the involvement of NDP kinases in the regulation of cell growth and differentiation.…”
Section: Discussionmentioning
confidence: 97%